A Shared, Targetable Inflammatory Mechanism Drives Hemorrhagic and Infectious Hydrocephalus. (16th November 2020) - Kahle, Kristopher T; Reeves, Benjamin; Karimy, Jason K; Zhang, Jinwei; Schiff, Steven J; Limbrick, David D; Alper, Seth; Warf, Benjamin C; Simard, J. Marc
Abstract: INTRODUCTION: Post-hemorrhagic and post-infectious hydrocephalus (PHH; PIH) are two of the most common forms of hydrocephalus. Neurosurgical CSF shunting remains the standard of care for PHH and PIH despite high rates of morbidity. Gaps in knowledge regarding the choroid plexus epithelium (CPe) and molecular pathophysiology of PHH and PIH are an obstacle, slowing the development of novel therapies. METHODS: We developed rat models of PHH and PIH via 50 μl of intracerebroventricular (ICV)-injected autologous blood (assessed at 48 hr or 14d) or continuous ICV infusion of LPS or E. coli for 72 hrs at 10 ng/μl/hr (assessed at 72 hr or 14d), respectively. MRI and in vivo CSF secretion measurements evaluated CSF dynamics, while Bulk RNAseq and dual mass spectroscopy assessed the CPe transcriptome and phospho-proteome. Immunoblotting and immunohistochemistry evaluated the functional expression of TLR4-associated molecules in the CPe. RESULTS: IVH, E. coli, and LPS triggered an acute (48 hr or 72 hr) ∼3.5-fold increase in CSF secretion, a >300% increase in ventricular volume, and a significant increase in the activating phosphorylation of TLR4-NF-kB-regulated inflammatory-mediators and SPAK-NKCC1. Emphasizing the importance of LPS and TLR4, ICV infusion of E. coli without LPS resulted in an ∼88% and ∼72% decrease in acute CSF secretion rate and ventricular volume, respectively, as compared to wild-type E. coli infusion. ICV dye injections showed developing aqueductal stenosis present only at chronic timepoints (14d), likely explaining why ventriculomegaly persisted and sometimes worsened at 14d despite the return of CSF secretion to basal levels at 7d post-insult in both models. Moreover, treatment with the NKCC1 inhibitor bumetanide attenuated the acute development of ventriculomegaly by ∼50% but not at 14d post-insult. Furthermore, treatment with a repurposed FDA-approved drug targeting TLR4-dependent inflammation reversed acute and chronic ventriculomegaly. CSF hypersecretion and ventriculomegaly were also acutely attenuated upon treatment with bumetanide, Zt-1a, and Tak-242 or genetic ablation of TLR4 or SPAK in both models. CONCLUSION: These data demonstrate a shared inflammatory response in both PHH and PIH that is targetable using a novel pharmacologic strategy.